2015
DOI: 10.46867/ijcp.2015.28.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Modulates Interval Timing in Rats: Effect of Pinealectomy

Abstract: Interval timing is a complex cognitive process that involves the estimation of time within the seconds-to-minutes range. This temporal processing depends on cortico-striatal interactions, as well as an optimal dopaminergic function. On the other hand, the circadian system controls physiological and behavioral functions with periods close to 24 hr. We have previously reported that short-time perception in mice is influenced by the circadian pacemaker, with dopamine signaling as a link between both temporal syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…It was recently reported that melatonin-depleted rats by pinealectomy (i.e., removal of the pineal gland, a brain structure that releases the circadian hormone melatonin) showed impaired learning in the peak-interval timing task. Furthermore, lack of melatonin increased striatal DA availability -which was reversed by external melatonin administration -indicating that this hormone may modulate interval timing on a circadian base [48].…”
Section: Interval Timing and Daily Rhythms Of Dopamine Levels In The ...mentioning
confidence: 97%
“…It was recently reported that melatonin-depleted rats by pinealectomy (i.e., removal of the pineal gland, a brain structure that releases the circadian hormone melatonin) showed impaired learning in the peak-interval timing task. Furthermore, lack of melatonin increased striatal DA availability -which was reversed by external melatonin administration -indicating that this hormone may modulate interval timing on a circadian base [48].…”
Section: Interval Timing and Daily Rhythms Of Dopamine Levels In The ...mentioning
confidence: 97%